Oviposition Habitat Selection of Dengue Vectors, Aedes aegypti and Aedes albopictus in Response to Fish Predator - Wan Fatma Zuharah; Nik Fadzly; Wilson Ong Kang Wei; Zarul Hazrin Hashim (Tropical Life Sciences Research, 2016)
To understand the effects of fish predator’s kairomones on Aedes mosquitoes’ oviposition, we established an experiment using gravid Aedes females. Kairomones concentrations were established using Hampala macrolepidota. One individual fish was placed inside containers with varying water levels (1 L, 5 L, and 10 L of water). The fish were kept in the containers for 24 hours and were removed immediately at the start of each trial in order to have the kairomones remnants. Twenty gravid adult females of Aedes aegypti and Aedes albopictus were allowed to lay eggs on oviposition site with various treatments: (1) control without any kairomones; (2) kairomone remnant in 1 L of water; (3) kairomone remnant in 5 L of water; and (4) kairomone remnant in 10 L of water. There are significant differences between the numbers of eggs laid by both Aedes species for each different treatment (F = 9.131, df = 16, p<0.001). However, fewer eggs were laid by Ae. albopictus compared to Ae. aegypti in the presence of kairomone remnants. This suggested that Ae. albopictus are significantly affected by the kairomones itself and have ability to detect the residual kairomone presence from H. macrolepidota.